Current and future therapies for type 1 diabetes - von Scholten, Bernt Johan; Kreiner, Frederik F.; Gough, Stephen C. L.; von Herrath, Matthias (Diabetologia, 2021)
In type 1 diabetes, insulin remains the mature therapeutic cornerstone; yet, the increasing number of individuals developing type 1 diabetes (predominantly children and adolescents) still face severe complications. Fortunately, our understanding of type 1 diabetes is continuously being refined, allowing for refocused development of novel prevention and management strategies. Hitherto, attempts based on immune suppression and modulation have been only partly successful in preventing the key pathophysiological feature in type 1 diabetes: the immune-mediated derangement or destruction of beta cells in the pancreatic islets of Langerhans, leading to low or absent insulin secretion and chronic hyperglycaemia. Evidence now warrants a focus on the beta cell itself and how to avoid its dysfunction, which is putatively caused by cytokine-driven inflammation and other stress factors, leading to low insulin-secretory capacity, autoantigen presentation and immune-mediated destruction. Correspondingly, beta cell rescue strategies are being pursued, which include antigen vaccination using, for example, oral insulin or peptides, as well as agents with suggested benefits on beta cell stress, such as verapamil and glucagon-like peptide-1 receptor agonists. Whilst autoimmune-focused prevention approaches are central in type 1 diabetes and will be a requirement in the advent of stem cell-based replacement therapies, managing the primarily cardiometabolic complications of established type 1 diabetes is equally essential. In this review, we outline selected recent and suggested future attempts to address the evolving profile of the person with type 1 diabetes. Graphical abstract